Tinjauan Teologis Konsep Sesama Manusia Menurut Lukas 10:25-37 dan Aplikasinya dalam Etika Pergaulan Modern - Paulus Kunto Baskoro; Roy Ferisa Satya Pandora (Jurnal Teologi Berita Hidup, 2026)
"Who is my neighbor?" This question was posed by a scribe, motivated by his understanding that "neighbor" was limited to Jews alone. Jews considered themselves the most holy, chosen by God, and had no regard for foreigners or people other than their own. This understanding tended to limit their behavior to loving others beyond a specific relationship. This study focuses on uncovering the theological meaning contained in Luke 10:25-37. The research method used is descriptive qualitative research. The purpose of this study is to discover the correct principle according to biblical standards regarding the meaning of "who is my neighbor" and to clearly convey the Lord Jesus' intent and purpose in giving the parable in Luke 10:25-37 and its implications for the lives of believers today, so that the love of every believer can be expressed to everyone, without discrimination.